JEJAK KOLONIAL DAN PERAN ORIENTALISME DALAM KUMPULAN CERPEN TEH DAN PENGHIANAT KARYA IKSAKA BANU - Nalurita, Baiq Annisa Yulfana; Apriyani, Tristanti (Universitas Ahmad Dahlan, 2022)
The colonial period was the planting of orientalist concepts towards the East, where the differences between East and West were very much shown. This of course did not escape the views of several Indonesian writers and writers who then tried to record this phenomenon in their literary works. One of the Indonesian writers, Iksaka Banu, who discusses the conflict between the natives and the Dutch, the Dutch and ethnic Chinese, to the conflict between the Dutch and the Dutch in various experiences and one of them is Iksaka Banu's latest collection of short stories entitled Teh dan Penghianat which was just published in 2019. This research using qualitative descriptive method aims to describe the form and role of orientalism in the collection of Teh and the traitor by Iksaka Banu by taking two short stories as material for analysis, namely 'Teh dan Pengianat' and ‘Belenggu Emas’. The data collection technique was carried out by document study techniques in short stories, namely by collecting data in the form of document archives, including books and journals. Meanwhile, the data triangulation process in the form of theoretical triangulation, data source triangulation and researcher triangulation, was carried out by the author to check the validity of the data. By using the theory put forward by Edward Said, this research concludes that in the short story Teh dan Pengtangan, there can be found several depictions of the East in the context of orientalism which symbolized by indigenous and ethnic Chinese. Meanwhile, in the short story Belenggu Emas, the depiction of the east in the context of orientalism is described as an indigenous community that needs to be improved or educated